Bleaching in vital deciduous teeth - a clinical case - José Carlos Pettorossi Imparato; Gabriela Azevedo de Vasconcelos Cunha Bonini; Fabiana Miura; Clarissa Calil Bonifácio; Daniela Prócida Raggio (Faculdade São Leopoldo Mandic, 2008)
There has been growing concern and search for esthetic beauty and harmony over the last few years. This concern does not form part ofadults' lives only, but also of children's. Among the substances used for bleaching dental structures, the most outstanding are those whoseactive principle is hydrogen peroxide-based . The present study reports a clinical case of a 4-year-old girl that suffered trauma of tooth 61 with consequent color alteration, but with no alteration in pulp vitality. The main complaint by the patient and her guardians concerned esthetics, therefore external dental bleaching was performed, using Opalescence Xtra® (Ultradent), in two sessions with an interval of one month between them. External in office bleaching was the treatment of choice, due to the tooth vitality, patient's age and presence of only one darkened tooth. After the bleaching treatments an improvement in the darkening was observed, and both the child and her guardians were satisfied with the esthetic result.